Diabetic retinopathy - Tobaru-Miyashiro, Luis (2019)
Diabetes mellitus in a serious public health problem worldwide that it is rising. Diabetic retinopathy is acomplication of this disease and due to its high prevalence is the main cause of blindness in the economically active population. This review seeks to highlight the importance of early diagnosis and timely and appropriate treatment, both of diabetes mellitus and its associated risk conditions, as well as diabetic retinopathy.